2009
DOI: 10.1177/0731684409338748
|View full text |Cite
|
Sign up to set email alerts
|

Impact, Tear, and Dielectric Properties of Cotton/Polypropylene Commingled Composites

Abstract: Natural fibers can be used as reinforcements in thermoplastic non-structural applications. Commingling them with matrix fibers lowers the melt flow distance of molten matrix during the processing. In this study, polypropylene (PP) and textile cotton fibers were commingled and fabricated to composite laminates. Process variables like temperature, pressure, and holding time affect the mechanical properties like impact strength and tear resistance. Fiber content and winding pattern or fiber orientation were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Because of that, the value of the ɛ ′ m increased with the increase in the content of the viscose, and thus hydroxyl groups, in the material. The obtained results are in agreement with the results obtained by Markiewicz et al and George et al, for polypropylene and lignocellulosic composite materials, as well as with the results obtained by Jose Tomlal et al for polypropylene and cotton composite materials. Namely, Markiewicz et al and George et al, concluded that the value of the dielectric permeability increases with the increase in the content of the lignocellulosic material, as well as Jose Tomlal et al concluded that the dielectric constant value increase with the increase in the cotton fiber weight percentage in the composite …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Because of that, the value of the ɛ ′ m increased with the increase in the content of the viscose, and thus hydroxyl groups, in the material. The obtained results are in agreement with the results obtained by Markiewicz et al and George et al, for polypropylene and lignocellulosic composite materials, as well as with the results obtained by Jose Tomlal et al for polypropylene and cotton composite materials. Namely, Markiewicz et al and George et al, concluded that the value of the dielectric permeability increases with the increase in the content of the lignocellulosic material, as well as Jose Tomlal et al concluded that the dielectric constant value increase with the increase in the cotton fiber weight percentage in the composite …”
Section: Resultssupporting
confidence: 93%
“…It is known that pure polypropylene is a nonpolar hydrophobic material, which in the alternating electric field shows only instantaneous ionic and electronic polarization. According to the literature, the addition of a hydrophilic lignocelluloses material (such as flax and hemp) to the polypropylene entails the insertion of polar groups into the nonpolar material resulting in an increase of the polarization due to the dipole reorientation. Therefore, the overall polarization of the composites (a mixture of polypropylene and lignocelluloses material), represents the sum of: electronic, ionic and dipole reorientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of a material to get polarized, and to accumulate charge on applying an external electric field through parallel plates behaving like capacitors is referred to as its dielectric constant and is denoted as ɛ′ . It can be calculated using the Eq .…”
Section: Resultsmentioning
confidence: 99%
“…Polarisability, on the other hand, is comprised of contributions from interfacial, dipole, atomic and electronic polarizations. Interfacial polarization (charge carriers are trapped at the interface of the material) has a huge impact on the dielectric properties of the material, when the material in question is heterogeneous in nature . Figure depicts the effect of frequency on (a) dielectric constant, (b) dielectric loss, and (c) conductivity of PP/MWCNT composites with varying CNT content (ranging from 0.3 to 20 wt%).…”
Section: Resultsmentioning
confidence: 99%